B. N. VIS - Cities Made of Boundaries. Mapping Social Life in Urban Form - García-Pérez, Sergio (ZARCH, 2020)
Benjamin N. Vis Cities Made of Boundaries. Mapping Social Life in Urban Form Londres: UCL Press, 2018, 416 págs. Encuadernación en rústica. Idioma: inglés. PDF de acceso abierto. ISBN: 978–1–78735–105–9 DOI: https:// doi.org/10.14324/111.9781787351059